Factors influencing hospital conveyance following ambulance attendance for people with diabetes: A retrospective observational study. Issue 4 (29th September 2020) - van Woerden, H.; Bucholc, M.; Clubbs Coldron, B.; Coates, V.; Heaton, J.; McCann, M.; Perrin, N.; Waterson, R.; Watson, A.; MacRury, S.
Abstract: Aim: To assess variables contributing to hospital conveyance for people with diabetes and the interactions between them. A secondary aim was to generate hypotheses for further research into interventions that might reduce avoidable hospital admissions. Methods: A national retrospective data set including 30 999 diabetes‐related callouts from the Scottish Ambulance Service was utilized covering a 5‐year period between 2013 and 2017. The relationship between diabetes‐related hospital conveyance and seven potential risk factors was analysed. Independent variables included: age, gender, deprivation, paramedic attendance, treatment at the scene, first blood glucose measurement and day of the week. Results: In Scotland, hyperglycaemia was associated with a higher number of people being conveyed to hospital than hypoglycaemia (49.8% with high blood glucose vs. 39.3% with low glucose, P ≤ 0.0001). Treatment provided in pre‐hospital care was associated with reduced conveyance rates (47.3% vs. 58.2% where treatment was not administered, P ≤ 0.0001). Paramedic attendance was also associated with reduced conveyance to hospital (51.4% vs. 59.5% where paramedic was not present, P ≤ 0.0001). Paramedic attendance in hyperglycaemic cases was associated with significantly reduced odds of conveyance (odds ratio 0.52, P ≤ 0.001). Conclusions: A higher rate of conveyance associated with hyperglycaemic cases indicates a need for more resources, education and training in this area. Higher conveyance rates were also associated with no paramedic being present and no treatment being administered. This suggests that paramedic attendance may be crucial in reducing avoidable admissions. Developing and validating protocols for pre‐hospital services and treatment may help to reduce hospital conveyance rates.